Gender differences in German upward income mobility - Ira N. Gang; John Landon-Lane; Myeong-Su Yun (Rutgers University, Department of Economics, 2002)
We examine the upward labor income mobility of men and women in Germany using the GSOEP Cross National Equivalent File. Women have greater overall income mobility. However, utilizing a measure of upward income mobility and calculating the posterior probability that men's upward income mobility is greater than women's, we find that men have overall greater upward income mobility. Women have greater upward mobility in the lower intial income classes, in the upper initial income brackets men's mobility is higher than women's.
Keywords: D3; D63; J7; 330; gender discrimination; income distribution dynamics; Markov chain; upward income mobility; Lohndifferenzierung; Fraueneinkommen; Soziale Mobilität; Geschlecht; Schätzung; Deutschland